2022
DOI: 10.1021/acsmaterialslett.1c00766
|View full text |Cite
|
Sign up to set email alerts
|

A Nanoscale Design Approach for Enhancing the Li-Ion Conductivity of the Li10GeP2S12 Solid Electrolyte

Abstract: The discovery of the lithium superionic conductor Li 10 GeP 2 S 12 (LGPS) has led to significant research activity on solid electrolytes for high-performance solid-state batteries. Despite LGPS exhibiting a remarkably high room-temperature Li-ion conductivity, comparable to that of the liquid electrolytes used in current Li-ion batteries, nanoscale effects in this material have not been fully explored. Here, we predict that nanosizing of LGPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…The activation energy follows this trend and slightly increases from 0.31 to 0.34 eV. This behavior does not support the proposed increase in ionic conductivity, as suggested by Dawson and Islam for nanocrystalline LGPS benefiting from local disorder, changes in local ion coordination or even a change in the dimensionality of the dynamic process . The simulations suggest that diffusion along the ab -plane, that is, in-plane diffusion, is facilitated when going from the bulk to nanocrystals with a grain volume of 10 nm 3 ; hence, they postulate a change from 1D to 3D diffusion.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…The activation energy follows this trend and slightly increases from 0.31 to 0.34 eV. This behavior does not support the proposed increase in ionic conductivity, as suggested by Dawson and Islam for nanocrystalline LGPS benefiting from local disorder, changes in local ion coordination or even a change in the dimensionality of the dynamic process . The simulations suggest that diffusion along the ab -plane, that is, in-plane diffusion, is facilitated when going from the bulk to nanocrystals with a grain volume of 10 nm 3 ; hence, they postulate a change from 1D to 3D diffusion.…”
Section: Resultsmentioning
confidence: 58%
“…According to the simulations, the ionic transport in LGPS shifts from a preferential diffusion along the c -direction to quasi 3D for the nanosized structure. Additionally, it is reported that for a structure made of grains with a volume of 10 nm 3 the diffusion length for Li-ion transport is significantly reduced, which results in increased intergranular diffusion …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some progress has been made regarding ion transport at solid electrolytes GBs using molecular dynamics studies with classical potentials. 10,[16][17][18][19][20] For example, it has been established why oxidebased solid electrolytes generally exhibit higher GB resistance 16 than sulfides and how GBs provide an explanation for the often observed differences in calculated and experimental Li-ion conductivities in some solid electrolyte families. 10 Although classical models are valuable as their low computational expense enables the investigation of large grain boundaries and nanostructures containing many tens or even hundreds of thousands of atoms over long timescales, their utility is limited by the fact that they lack access to electronic properties.…”
Section: Introductionmentioning
confidence: 99%